Controle de plantas daninhas em função de características morfológicas - Canova, Luís Henrique (2022)
Weeds are one of the main problems that impede rural producers from reaching higher levels of productivity and productive efficiency on their properties. It is fundamental for the proper management of weeds that there is a correct identification, while the plant is young and susceptible to less complex chemical treatments. This work aims to generate data that can contribute to the improvement of management tools, as well as a more rational use of herbicides, aiming at the development of a more efficient resources usage in agriculture. The experiments were carried out in a greenhouse at the Faculty of Agronomy and Veterinary Medicine of the University of Passo Fundo (UPF), where Hairy Beggarticks (Bidens spp.), Sourgrass (Digitaria insularis) and Italian Ryegrass plants (Lolium perenne var. multiflorum) were cultivated in substrate until 15, 30, 45, 60 and 75 days after sowing, in order to analyze plant height, leaf area, soil cover by the aerial part of the plant - calculated by software after capturing aerial part images - and the subsequent evaluation of chemical control effectiveness when subjected to different doses of herbicides. The experimental design was completely randomized, with treatments arranged in a factorial scheme, with four replications. The results show a difference between the control of Hairy Beggarticks plants depending on the doses of glyphosate used and the vegetative stage, being that the lowest dose (500 g a.e. ha-1) did not effectively control the plants at 75 days after sowing (DAS) and doses of 500 g a.e. ha-1 and 1000 g a.e. ha-1 did not effectively control the plants at 60 DAS. In the Sourgrass experiment, none of the product doses tested resulted in an efficient control of the plants at 75 and 60 DAS and the lowest dose of clethodim (96 g a.i. ha-1) mixed with glyphosate (1500 g a e. ha-1) was also not efficient in weed control at 45 DAS. The results obtained in the experiment with Italian Ryegrass show us that even the lowest dose of clethodim (96 g a.i. ha-1) mixed with glyphosate (1000 g a.e. ha-1) was efficient to control plants at all stages. However, it was observed that younger plants (15 and 30 DAS) were controlled more quickly. Soil cover by the aerial part of the weeds calculated from images obtained high values of correlation with the leaf area of the plants, (Hairy Beggarticks:r = 0.92; Sourgrass r = 0.86; Italian Ryegrass r = 0.64), validating the aerial image acquisition method. As discussed and demonstrated by several researchers, the identification of weeds in early stages of growth is feasible. From these results, we can say that it is possible to generate infestation maps of Hairy Beggarticks, Sourgrass and Italian Ryegrass plants with accurate detection of weed and crops.